2009
DOI: 10.1145/1517480.1517492
|View full text |Cite
|
Sign up to set email alerts
|

Double-blind reviewing

Abstract: In double-blind reviewing (DBR), both reviewers and authors are unaware of each others' identities and affiliations. DBR is said to increase review fairness. However, DBR may only be marginally effective in combating the randomness of the typical conference review process for highly-selective conferences. DBR may also make it more difficult to adequately review conference submissions that build on earlier work of the authors and have been partially published in workshops. I believe that DBR mainly increases th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Norman and Griffith [108] note that it can exaggerate the weight of redundant results in meta-analyses, reduce the space available for other papers, and waste reviewer time. Schulzrinne [113] adds a few more, including authors receiving "double credit" for the same work, and listener boredom from re-runs at conferences. There might also be copyright violations [50].…”
Section: Policies and Practice On Qualificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Norman and Griffith [108] note that it can exaggerate the weight of redundant results in meta-analyses, reduce the space available for other papers, and waste reviewer time. Schulzrinne [113] adds a few more, including authors receiving "double credit" for the same work, and listener boredom from re-runs at conferences. There might also be copyright violations [50].…”
Section: Policies and Practice On Qualificationmentioning
confidence: 99%
“…While most of the research literature studied was found to be in favor of double-blind review, quite a few papers suggest that the effectiveness of blinding should not be overestimated: if it is not done carefully, the identity of the author can be revealed by self-citing [26] or proprietary software used for the research [113].…”
Section: Policies and Practice On Qualificationmentioning
confidence: 99%